2017
DOI: 10.1080/21505594.2017.1385691
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity analysis of human parvovirus B19-VP1u protein in the induction of anti-phospholipid syndrome

Abstract: Mounting evidence suggests a connection between human parvovirus B19 (B19) and autoimmune diseases, and especially an association between the B19-VP1 unique region (VP1u) and anti-phospholipid syndrome (APS). However, little is known about the antigenicity of B19-VP1u in the induction of APS-like syndrome. To elucidate the antigenicity of B19-VP1u in the induction of APS, N-terminal truncated B19-VP1u (tVP1u) proteins were prepared to immunize Balb/c mice to generate antibodies against B19-tVP1u proteins. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Most viral proteins are involved in inflammatory and autoimmune disorders: VP-1, which includes a “VP-1 unique region” (VP-1u) characterized by a phospholipase A2-like activity, probably playing a role in viral entry into the cell [ 108 ] and the generation of inflammatory mediators (leukotrienes and prostaglandins) and phospholipids epitopes, potentially triggering antiphospholipid (aPL) antibodies [ 109 ]. Of note is the fact that VP1-unique region contains many epitopes recognized by neutralizing antibodies, which determine life-long protection [ 106 ].…”
Section: Role Of Specific Viral Infections In Slementioning
confidence: 99%
See 1 more Smart Citation
“…Most viral proteins are involved in inflammatory and autoimmune disorders: VP-1, which includes a “VP-1 unique region” (VP-1u) characterized by a phospholipase A2-like activity, probably playing a role in viral entry into the cell [ 108 ] and the generation of inflammatory mediators (leukotrienes and prostaglandins) and phospholipids epitopes, potentially triggering antiphospholipid (aPL) antibodies [ 109 ]. Of note is the fact that VP1-unique region contains many epitopes recognized by neutralizing antibodies, which determine life-long protection [ 106 ].…”
Section: Role Of Specific Viral Infections In Slementioning
confidence: 99%
“…These patients also had a higher titer of IgG antibodies to B19V compared to those without APS, suggesting a link between previous viral exposure and APS [ 42 ]. The role of protein VP1u as an antigen triggering APS-like syndromes has been established [ 109 ].…”
Section: Role Of Specific Viral Infections In Slementioning
confidence: 99%
“…The VP1-unique (VP1u) regions of both B19V and HBoV have been shown to exhibit PLA2-like activity and are known to play essential roles in viral infectivity [3637]. Moreover, the PLA2-like activity of B19V-VP1u and HBoV-VP1u has been implicated in a wide range of pathogenic responses, such as autoimmune diseases, cardiovascular disorders and respiratory diseases [7, 910, 3840]. Our recent studies revealed a disruptive effect of both HBoV-VP1u and B19-VP1u on tight junctions in A549 cells [7] and demonstrated the induction of lung injury by both B19V-VP1u and HBoV-VP1u in naïve mice through the differential regulation of the NF-κB and MAPK signaling pathways [14].…”
Section: Discussionmentioning
confidence: 99%
“…The sPLA2-like activity of B19V-VP1u and HBoV-VP1u has also been linked to a wide range of pathogenic responses, including autoimmune disorders, cardiovascular disorders and respiratory infection [ 17 , 48 ]. Indeed, evidence has indicated that the unique region of VP1 in B19V and HBoV plays a crucial role in infection and induce inflammation in host cells or tissues due to its phospholipase A2 (PLA2)-like activity [ 14 16 , 48 50 ]. Although previous studies have reported that B19-VP1u protein induces myocardial inflammation and liver injury in naïve mice [ 48 49 ], little is known whether HBoV-VP1u affect the other organs in mice receiving HBoV-VP1u protein.…”
Section: Discussionmentioning
confidence: 99%